2019
DOI: 10.33584/jnzg.2019.81.408
|View full text |Cite
|
Sign up to set email alerts
|

A paddock survey of on-farm plantain use

Abstract: The use of narrow-leaved plantain (Plantago lanceolata) in pasture sowing mixtures has recently increased following research demonstrating the value of the ‘Tonic’ cultivar in reducing cattle urinary N concentration, with likely benefits for reducing N leaching from pasture systems. The purpose of this study was to document the ways in which farmers are using plantain, investigate the factors that enhance successful establishment and persistence, and to test a method of visual estimation of plantain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…Mowing a mixed sward at around 35 d intervals gave plantain an advantage in the environment observed here. This is one of very few cases where plantain became dominant rather than a declining proportion of the sward (Dodd et al, 2019). Under grazing, the proportion of plantain in the sward declined in favour of grass in other reports (Ayala et al, 2011;Dodd et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Mowing a mixed sward at around 35 d intervals gave plantain an advantage in the environment observed here. This is one of very few cases where plantain became dominant rather than a declining proportion of the sward (Dodd et al, 2019). Under grazing, the proportion of plantain in the sward declined in favour of grass in other reports (Ayala et al, 2011;Dodd et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…Alternatively, feeding lower protein diets (Huhtanen et al, 2008) or changing pasture species to plantain (Plantago lanceolata) (Box et al, 2017) could be used to decrease urinary nitrogen deposition or spread urine more widely. Dodd et al (2019) found that the proportion of plantain in pastures declines rapidly after sowing in New Zealand. Very few paddocks had more than 20% of available dry matter as plantain three years after sowing.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Year 8 plantain yield was low (108 kg DM/ha) indicating that it had not persisted beyond Year 5. Previous surveys have found plantain decreases to <20% pasture cover in grass/plantain pastures after 3 years (Dodd et al 2019) but may retain a presence for 7+ years (Tozer et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…In 2013 and 2014, following soil tests (Table 2), 350 kg/ha of Sulphur Super 20 (0% N, 8% P, 0% K, 20.6% S, 18% Ca) was applied to Replicates 1 and 2 and 180 kg/ha to Replicates 3 and 4. In 2015, 2016, 2019and 2020 was applied to all replicates in early spring at 200 kg/ha. No fertiliser was applied in 2018.…”
Section: Soil Fertility and Fertiliser Applicationsmentioning
confidence: 99%
“…Ultimately, selection of species for diverse pastures will need to consider the establishment and grazing management requirements of all species within the mix. The challenge of managing diverse pastures in a commercial setting was evidenced recently in a survey of farmers in Canterbury and Waikato who had tried to incorporate plantain with mixed results (Bryant et al 2019;Dodd et al 2019). Realistically, the dominant grass species' grazing management will likely take priority over the other species present in the mixture as the consequences to persistence, productivity or nutritive value will likely outweigh any benefit from the species mixture.…”
Section: Use Of Diverse Pasture Speciesmentioning
confidence: 99%